2010
DOI: 10.1111/j.1365-2966.2010.16842.x
|View full text |Cite
|
Sign up to set email alerts
|

Native synthetic imaging of smoothed particle hydrodynamics density fields using gridless Monte Carlo radiative transfer

Abstract: An algorithm for creating synthetic telescope images of smoothed particle hydrodynamics (SPH) density fields is presented, which utilizes the adaptive nature of the SPH formalism in full. The imaging process uses Monte Carlo radiative transfer methods to model the scattering and absorption of photon packets in the density field, which then exit the system and are captured on a pixelated image plane, creating a 2D image (or a 3D data cube, if the photons are also binned by their wavelength). The algorithm is im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…To compute the distribution of line‐of‐sight peculiar velocity, we ray trace through the SPH simulation using the algorithms described in Altay, Croft & Pelupessy () and Forgan & Rice (). Particles only contribute to the density and velocity fields along the ray if their smoothing volumes intersect it (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compute the distribution of line‐of‐sight peculiar velocity, we ray trace through the SPH simulation using the algorithms described in Altay, Croft & Pelupessy () and Forgan & Rice (). Particles only contribute to the density and velocity fields along the ray if their smoothing volumes intersect it (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Particles only contribute to the estimated line‐of‐sight velocity if their smoothing volume intersects the ray. Figure taken from Forgan & Rice ().…”
Section: Methodsmentioning
confidence: 99%
“…Episodic accretion maybe due to gravitational instabilities (Vorobyov & Basu 2005;Machida et al 2011;Vorobyov & Basu 2015;Liu et al 2016), thermal instabilities in the inner disc region (Hartmann & Kenyon 1985;Lin et al 1985;Bell & Lin 1994), or due to gravitational interactions in a binary system (Bonnell & Bastien 1992;Forgan & Rice 2010). It has also been suggested that they may be due to the combined effect of gravitational instabilities operating in the outer disc region transferring matter inwards and the magneto-rotational instability (MRI) operating episodically in the inner disc region delivering matter onto the young protostar (Armitage et al 2001;Zhu et al 2007Zhu et al , 2009aZhu et al ,b, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Such radiation-hydrodynamics (RHD) schemes have been successfully implemented for grid-based (Harries 2015;Smith et al 2017) and moving mesh (Vandenbroucke & Wood 2018;Smith et al 2020) hydro codes, but are still under development for Smoothed Particle Hydrodynamics (SPH) codes. This is due to the particle nature of SPH and the fact that, with a few exceptions (Forgan & Rice 2010;Lomax & Whitworth 2016), MCRT algorithms are typically performed on a grid.…”
Section: Introductionmentioning
confidence: 99%